Uma Virada Imprevista: O "Fim" da Adoção Internacional no Brasil - Claudia Fonseca (Universidade do Estado do Rio de Janeiro, 2006)
The 1990s witnessed a dramatic decline in the international adoption of Brazilian children, from more than 2,000 a year in the earlier years to fewer than 400 by the end of the decade. Based on archival material, the current article outlines possible reasons for this decrease, considering hypotheses linked to the international market of adoptable children, legal restrictions on international adoption imposed by the Brazilian government, and scandals in the mass media that stigmatize local intermediaries and public officials involved in this activity. The study concludes that public opinion and scandals in the media have a heavy impact but are not necessarily the most adequate ingredients for a sensible adoption policy.